Intrarenal Complement System Transcripts in Chronic Antibody-Mediated Rejection and Recurrent IgA Nephropathy in Kidney Transplantation - Cernoch, Marek; Hruba, Petra; Kollar, Marek; Mrazova, Petra; Stranavova, Lucia; Lodererova, Alena; Honsova, Eva; Viklicky, Ondrej (Frontiers in Immunology, 2018)
Background: The complement system activation and regulation have been linked to post-transplant pathologies including chronic antibody mediated rejection (cAMR) and the recurrence of IgA nephropathy (ReIgAN) but distinct mechanisms remain to be elucidated. Methods: In this retrospective single center study, the outcome of kidney transplantation was studied in 150 patients with late histological diagnosis to be either cAMR or ReIgAN. To study a role of complement cascade and regulation, the RNA was extracted from available frozen kidney biopsy samples and using RT-qPCR transcripts of 11 target genes were determined. Immunohistologically, CD46 (MCP) and C5 proteins were stained in biopsies. Results: Interestingly, there were no differences in kidney graft survival between cAMR and ReIgAN since transplantation. cAMR was associated with significantly higher intragraft transcripts of C3, CD59 and C1-INH as compared to ReIgAN (p<0.05). A statistically significant correlation between increased intrarenal CD46 expression and decreased graft survival in cAMR patients was found (p<0.01, r=-0.508). Similarly, C3 transcripts correlated significantly with lower eGFR in cAMR group (p<0.05, r=-0.417). There were also significant correlations of both CD46 and CFI transcripts with lower eGFR in ReIgAN group (p<0.05, r=-0.401 and p<0.05, r=-0.442, respectively). Neither the low mRNA transcripts nor the high mRNA transcripts biopsies were associated with distinct trend in MCP or C5 proteins staining. Conclusions: The complement system regulator MCP is likely to play a role in main pathologies associated with kidney graft dysfunction.